Outcome of Whipple's procedure for Groove pancreatitis: A retrospective cross-sectional study. (July 2022) - Dhali, Arkadeep; Ray, Sukanta; Ghosh, Ranajoy; Misra, Debashis; Dhali, Gopal Krishna
Abstract: Background: Groove pancreatitis (GP) is a rare form of chronic pancreatitis primarily affecting the pancreatoduodenal groove. Very few studies have been published from India. The aim of the present study is to report our experience with Whipple's procedure for GP. Methodology: In this cross-sectional study, data of all patients who underwent Whipple's procedure for GP between August 2007 and July 2021 were retrospectively reviewed. Results: Of the total 504 Whipple's procedures, histopathologically proven GP was identified in 9 patients. All of them were male. Mean age at presentation was 42.66 ± 4.35 years. All of them had history of alcohol abuse. Eight (88.8%) of them had history of smoking. Postprandial abdominal discomfort and pain (n = 9, 100%) was the most common presenting symptom. Three (33.3%) patients had solid variety and six (66.6%) patients had cystic dystrophy of the duodenal wall. Two (22.2%) patients had mass in the head of the pancreas which was thought to be malignant. None of the patients underwent prior endoscopic management (stenting). Duration of surgery and blood loss was 330 (range, 300–379) minutes, and 250 (range, 200–750) ml respectively. There was no postoperative mortality. Postoperative complications developed in 5 (55.5%) patients. All the complications were managed conservatively. Median postoperative hospital stay was 10 (range, 9–16) days. Over a median follow-up of 41 (range, 12–120) months, complete remission of symptoms was achieved in 7 (78%) patients. Conclusion: Whipple's procedure is safe with acceptable perioperative outcomes and good long-term symptom control. Highlights: Groove pancreatitis (GP) is a rare form of chronic pancreatitis which involves the pancreatoduodenal groove. It is difficult to differentiate GP from pancreatic head malignancy preoperatively Whipple's procedure in GP has acceptable perioperative morbidity and mortality and long-term good results.